I like it better when you're funny working in television and other precarious adventures - Grodin, Charles 1935-2021 (Random House, 2002)
Complemented by humorous behind-the-scenes anecdotes, the author provides a memoir of his transition from award-winning actor to TV talk-show host and commentator and shares his insights into American culture and media.
Keywords: Grodin, Charles; Grodin, Charles -- 1935-2021; Actors -- United States -- Biography; Autobiografie; USA; Biografie